Russia-India: new horizons of the strategic alliance - Akarashov, I.S. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2018)
The article examines the development of Russian-Indian trade and economic relations from 1992 to 2017. The relevance of the topic is that currently the economic sanctions of some Western countries and the USA against Russia forced to strengthen the Eastern vector of its foreign policy. India is a leading country in the South Asian region, has nuclear capabilities, has demonstrated high rates of socio-economic and military development, and it has all chances to be among the world powers. The rapid growth of India draws attention of politicians and scientists. Deeper cooperation with India may become a good stimulus for the development of the Russian economy and to deepen bilateral strategic relations, in the conditions of aggravation of competitive struggle in world politics and economy is extremely important for both countries. The study of the historical experience, its content, potential, problems and perspectives seem to be relevant and useful. In the study of this topic, the author has considered the formation of modern normative-legal base of Russian-Indian trade and economic relations, has studied the structure and dynamics of trade turnover, revealed the main causes of the existing problems and identified prospects. As a methodological basis of the present study, we used the historical descriptive method which allowed the author to analyze the history of Russian-Indian economic relations. The results of the analysis the author concludes that today, there are a number of external and internal factors that negatively affect economic relations between the two countries, but Indian and Russian governments are determined to strengthen relations in this area, creating a favorable environment for the development of business contacts between representatives of business circles of Russia and India, and the commitment to take economic relations to a level commensurate with the status of “privileged strategic partnership”.